Gaze Patterns in Auditory-Visual Perception of Emotion by Children with Hearing Aids and Hearing Children - Wang, Yifang; Zhou, Wei; Cheng, Yanhong; Bian, Xiaoying (Frontiers in Psychology, 2017)
This study investigated eye-movement patterns during emotion perception for children with hearing aids and hearing children. Seventy-eight participants aged from 3 to 7 were asked to watch videos with a facial expression followed by an oral statement, and these two cues were either consistent or inconsistent in emotional valence. Results showed that while normal-hearing children paid more attention to the upper part of the face, children with hearing aids paid more attention to the lower face after the oral statement was presented. When there was an inconsistency between the visual and auditory cues, children with hearing aids were likely to increase attention to the upper face. The results revealed the underlying mechanism of deficits in emotion perception for hearing-impaired children.